Pengaruh Model Think Pair Share Berbantuan Papan Berpaku Terhadap Hasil Belajar Siswa Materi Bangun Datar Di Sekolah Dasar - Rahma Syifi; Linda Vitoria; Ahadin Ahadin (Universitas Syiah Kuala, 2023)
The purpose of this study was to determine the effect of the Think Pair Share model assisted by nailed board media on student learning outcomes in class IV SD Negeri 1 Lambheu Aceh Besar. This research takes a quantitative approach, the type of research is True experimental with the Pretest-Posttest Control Group Design. The research was conducted at SDN 1 Lambheu Aceh Besar. The research sample was all students of class IVA and IVB at SDN 1 Lambheu Aceh Besar. The data collection technique taken was the pretest and posttest, for the data analysis technique taken SPSS Statistics 24 and hypothesis testing with an independent t-test obtained a sig (2-tailed) value of 0.000 0.05. So the decision making criteria is that H0 is rejected and Ha is accepted. So it can be concluded that there is a significant influence using the Think Pair Share model assisted by nail board media on student learning outcomes in class IV SDN 1 Lambheu Aceh Besar material.